Heat wave hazard, vulnerability and risk assessment for India [Abstract only] - Sahana, V.; Suresh, N.; Mondal, A.; Mishra, T. (2023)
Global warming and rising temperatures have increased the occurrence and severity of heat waves across the globe. In India, the heatwave situation could break human survivability, thus jeopardizing food security, public health, as well as economic productivity of the country. With the growing population and as a developing economy, heatwave risk assessment in India is at most important and the analysis must account for changing climate and socio-economic conditions for planning effective heat wave mitigation and adaptation policies. We present a comprehensive district-level analysis of heatwave risk assessment considering the hazard and vulnerability aspects with a focus on regions that are prone to pre-monsoon heatwaves. The heatwave magnitude index is used to compute heatwave hazard at a pentad scale (5 years). Further, the robust aggregation method - Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS) method is used for heatwave vulnerability assessment. Health, infrastructure, technological, financial, social and exposure indicators from National Family Health Survey-5 (NFHS) and other remote sensing datasets are used for mapping heatwave vulnerability. In addition, the study identifies the hotspots of heatwave risk and their driving factors to decipher the individual roles in enhancing the risk of heatwaves and associated impacts such as mortality and health degradation. Therefore, our analysis can inform the climate and heat action plans of municipalities and corporations.